Selling World Cinema by the Pound: Disclosing the Worldist Idea of Cinema - Andrea Gelardi (Cinergie, 2017)
As a category which seeks to represent the totality of global film productions, World Cinema is here discussed by focusing on its use both in the theoretical and in the practical fields, so as to offer a critical comprehension of this concept. For this purpose, firstly I focus on some of the most meaningful definitions of World Cinema within film studies; secondly, I attempt an understanding of this category through its commercial usage in order to underline its touristic vocation and how it is meant to attract only a geographically situated market. In conclusion, I suggest how this peculiar approach might inflect the approach to otherness and to diversity and where this should be investigated.